A predictive modeling approach to test distributional uniformity of Uruguayan harvestmen (Arachnida: Opiliones) - Simó, Miguel (2014)
Background: Harvestmen are a good taxon for biogeographic studies due to their low vagility and their dependence on environmental conditions which make most of them live in humid and shaded habitats. Current knowledge of the geographical distribution of Uruguayan opiliofauna suggests that no evident zoogeographic areas are present, mainly because of the apparent uniformity of the landscape of this country. Recent biogeographic studies indicate that Uruguay represents a biogeographical crossroad between three South American provinces, and the aim of this study is focused on determining if this fact is reflected in the distribution of the Uruguayan opiliofauna. To test this presumption, we used the species distribution model methodology. Distribution data about four harvestmen species from Uruguay and neighboring countries were analyzed. We used the maximum entropy principle to perform a distribution model for each species. Results: We recognized Acanthopachylus aculeatus and Pachyloides thorellii as two Pampasic representatives of the Uruguayan opiliofauna. The other species studied, Discocyrtus prospicuus and Metalibitia paraguayensis, reflect Mesopotamian and Paranaense influences in the Uruguayan territory. Isothermality was the climatic variable with the best contribution in the models of the four species, reflecting constrained latitudinal ranges. Conclusions: Results of the present study suggest that two roughly different opiliological areas for Uruguay can be recognized, based on climatic variables.